Bohm's 1952 Pilot Wave Theory Revisited - Sarfatti, Jack (Cosmos and History: The Journal of Natural and Social Philosophy, 2019)
I investigate extending Bohm's original 1952 single-state pilot wave QM theory to the larger PQM regime of living matter in which conscious qualia emerges from direct back-reaction of classical level electrons and electromagnetic fields primarily on their macro-quantum coherent intrinsically mental pilot fields. I use insights from Roderick Sutherland's two-state fully relativistic Lagrangian extension of Bohm 1952 explaining many-particle nonlocal entanglements as locally retrocausal Costa de Beauregard "zig-zags" as further explained by Huw Price.<!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]-->